SAMAGRA SHIKSHA PROGRAMME TO PROMOTE SECONDARY EDUCATION - Bichitra pegu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study suggests the ways of prevention of gender inequality that prevails among every class and religion which creates a hindrance on the path of the Indian education system of India. Education is an essential tool for building an equitable society and also bring a transformation in the social, economic and political field. For which the Government has taken measures to provide an egalitarian education system. Also the perspective of the agency is to perceive country’s personnel capability in the tutelage section with justice and incorporation. Hence the “Ministry of Human Resource Development” is trying to execute proposition which aim at improving and enriching the learning and fundamental tutoring of the youngster and generate entry to all degree of learning including tertiary and technological education. The Centrally Sponsored Schemes launched throughout the country in partnership with State and Union Territory are “Samagra Shiksha Abhiyan”, “Sarva Shiksha Abhiyan”, “Rashtriya Madhyamik Shiksha Abhiyan”, “Teacher Education”. These schemes are to address several holes in the school education system of India.